2015
DOI: 10.1063/1.4921348
|View full text |Cite|
|
Sign up to set email alerts
|

Perspective: Single polymer mechanics across the force regimes

Abstract: I review theoretical and experimental results on the force-extension response of single polymers, with a focus on scaling pictures of low-force elastic regimes, and recent measurements of synthetic and biological chains that explore those regimes. The mechanical response of single polymers is an old theoretical problem whose exploration was instigated by the curious thermomechanical behavior of rubber. Up until the 1990s, the main utility of those calculations was to explain bulk material mechanics. However, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 67 publications
5
58
0
Order By: Relevance
“…However, single molecule pulling experiments on ssDNA showed a qualitatively different response, such that x ∼ ln f in the high-force regime [38]. It was found that this unusual behavior arises due to polyelectrolyte or charge effects for flexible polymers in the high-force regime, supported by scaling theory [71] and simulations of the stretching of flexible polyelectrolytes under high force [72,73].…”
Section: Thermal Blobsmentioning
confidence: 94%
“…However, single molecule pulling experiments on ssDNA showed a qualitatively different response, such that x ∼ ln f in the high-force regime [38]. It was found that this unusual behavior arises due to polyelectrolyte or charge effects for flexible polymers in the high-force regime, supported by scaling theory [71] and simulations of the stretching of flexible polyelectrolytes under high force [72,73].…”
Section: Thermal Blobsmentioning
confidence: 94%
“…The linear response χ(T, F = 0) of the semiflexible polymer to the compression force can also be obtained exactly by expanding the full solution in Eqs. (26), (27), and (28) to second order in the force. For a clamped polymer we use the expansions of the Mathieu functions for ϕ 0 = ϕ L = 0 and the corresponding eigenvalues up to second order in the deformation parameter q from Refs.…”
Section: B Linear Responsementioning
confidence: 99%
“…Due to their semiflexibility, biopolymers show a peculiar response to external forces [20][21][22], where the static and dynamic properties are dominated by their enthalpic elasticity, but conformational entropy still plays a significant role. Experimental techniques such as optical [23,24] and magnetic tweezers [25], transmission electron microscopy [26], and (atomic) force spectroscopy [19,27] have been used to quantify the mechanical properties in terms of force-extension relations [28]. These capture the nonlinear effects emerging in the stretching and buckling of semiflexible polymers such as DNA [29][30][31], actin [32], and synthetic carbon nanotubes [26], but also single molecules such as titin [33], which is an important component in striated muscle tissues, and collagen [34], present in, e.g., skin and bones.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond their biological significance, NAs are of interest to polymer physicists as models of strong polyelectrolytes (10). …”
Section: Introductionmentioning
confidence: 99%